Year-round Living in Alpine Arc Resorts Facing High Tourism Intensity and Seasonality - Quentin Benoît Guillaume Drouet (Via@)
Some winter sports resort communities in the Alpine Arc appear to have been weakened by a demographic downturn, while others still report an increase in their permanent population. This article examines the causes of these contrasting situations in France (Les Deux Alpes, Les Belleville, Montvalezan, La Clusaz), Switzerland (Nendaz), Austria (Kitzbühel), Italy (Badia/Abtei), and Slovenia (Kranjska Gora). Based on interviews with local stakeholders, an analysis of socio-economic data and a review of the relevant literature, we analysed the year-round dynamics in these communities. The high tourism seasonality tends to attract temporary residents. While real-estate pressures exist in all the areas studied, other factors also affect the ability of communities to maintain local year-round living dynamics. Our findings raise questions about the role of public initiatives in striking a balance between promoting tourism for a clientele that changes weekly and providing a living space for year-round residents.